STRENGTHENING EXPERIENCE-BASED LEARNING IN DISTANCE EDUCATION OPEN UNIVERSITY IN THE ERA OF SOCIETY 5.0 - Djoko Sri Bimo; E'em Kurniasih (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2026)
The transformation of higher education in the era of Society 5.0 demands the integration of intelligent technology with a human-centered approach to learning. The Open University as a distance education institution is required not only to provide wide access, but also a meaningful learning experience through an experience-based learning approach. This study aims to analyze the strategy of strengthening experience-based learning in the Open University distance education system and its impact on student engagement and learning achievement. The research uses descriptive qualitative approach with literature study method and Digital Learning Policy Analysis. The results showed that the integration of Learning Management System (LMS), interactive online tutorials, case-based projects, and the use of collaborative technology can increase student active participation and strengthen the construction of experience-based knowledge. In addition, tutor support as a reflective learning facilitator is a key factor in building adaptive academic interactions. In the context of Society 5.0, strengthening experience-based learning encourages the creation of a digital learning ecosystem that is inclusive, flexible, and oriented to the development of 21st century competencies. Thus, this strategy strengthens the position of the Open University as a pioneer of innovative distance education and responsive to the dynamics of technology and the needs of society.